Allometric scaling of body mass in running economy data: An important consideration in modeling marathon performance - Lundstrom, C. J.; Biltz, G. R.; Snyder, E. M.; Ingraham , S. J. (Journal of Human Sport & Exercise, 2017)
The purpose of this study was to compare metabolic variables during submaximal running as predictors of marathon performance. Running economy (RE) and respiratory exchange ratio (RER) data were gathered during a 30 min incremental treadmill run completed within 2 weeks prior to running a 42.2-km marathon. Paces during the treadmill run progressed every 5 min from 75-100% of 10-km race velocity. Variables at each stage were analyzed as predictors of relative marathon performance (RMP) in competitive (COMP) and recreational (REC) runners. Twenty-nine runners were classified as COMP (n = 12; age 30 ± 8 years) or REC (n =17; age 20 ± 1 year) based on performance in shorter races. RMP was calculated as percent difference from predicted marathon finish time. Two methods of calculating RE were used: unscaled (ml/kg.km) and with allometric scaling of body mass (ml.kg-0.75/km). The COMP runners were significantly more economical than REC (p=0.005; p=0.015 with scaling). For the whole population, RE with and without scaling was significantly correlated with RMP. Within groups, RMP was not significantly correlated with RE unless scaling was used: COMP runners at 75% (p=0.044), 80% (p=0.040), and REC runners at 85% (p=0.038). Runners classified as COMP were more economical than REC, but RER was not different. The use of allometric scaling is important when assessing homogeneous groups. In this study, allometrically-scaled RE at 80-85% of 10-km velocity was the best predictor of RMP within groups.